The effect of Evening primrose on blood sugar and lipid profile of prediabetic postmenopausal women: Randomized clinical trial - Asma Absalan; Seyede Maryam Lotfipour; Marzeyeh Lori poor; Maryam Karimi Fard; Hassan Ahmadinia (Mashhad University of Medical Sciences, 2021)
Introduction: Prevention of diabetes and its associated complications is especially important during menopause because significant changes occur in blood lipid levels along with insulin resistance due to aging and predispose to cardiovascular diseases. Regarding to the lower side effects of herbal medicines than chemical medicines, this study was performed with aim to evaluate the effect of evening primrose on blood sugar and fat profile of pre-diabetic postmenopausal women.Methods: This triple-blind randomized clinical trial was performed in 2018-2019 on 82 pre-diabetic postmenopausal women referred to the comprehensive health service centers in Rafsanjan. The intervention group received two 1000 mg capsules of evening primrose daily and the control group received placebo for three months. Before and after the intervention, fasting sugar (FBS, HbA1C) and blood lipid profile (including triglyceride, total cholesterol, low and high density lipoprotein) were assessed in the two groups by blood test. Data were analyzed by SPSS software (version 16) and independent t-test, Paired t-test and covariance test. P<0.05 was considered statistically significant.Results: In this study, mean LDL in pre-diabetic postmenopausal women receiving evening primrose capsule showed a statistically significant difference. But the mean of FBS, HDL, TG and cholesterol didn't show a statistically significant difference.Conclusion: Daily consumption of two 1000 mg capsules of evening primrose reduces LDL levels in pre-diabetic postmenopausal women, which can reduce the risk of cardiovascular diseases.